2030 Agenda and Renewable Energy: synergies and challenges to achieve sustainable development (Research, Society and Development, 2021)
The energy sector at a global level is one of the most discussed agendas in the current century, whose centralization of the debate permeates the emergence of establishing new patterns of production and consumption in a perspective of sustainability. In this sense, the legitimacy and importance of the topic was recognized in 2015 by the United Nations (UN) on the occasion of the launch of the 2030 agenda. From this juncture, from a multidisciplinary and integrated approach, dealing with the context of renewable energies, especially wind, the main object of this study is to analyze the light of the 2030 agenda and its respective objectives, which are possible synergies and challenges. To this end, the methodological path followed the ways of exploratory and descriptive research with a data collection instrument through bibliographical and documentary research. The results obtained show synergies between the wind sector and the SDGs. On the challenges side, the lack of alignment between public policies and SDGs in a perspective of integration to achieve energy sustainability was evidenced.